Second-Line Irinotecan, Leucovorin, and 5-Fluorouracil for Gastric Cancer Patients after Failed Docetaxel and S-1 - Joo Young Jung; Min-Hee Ryu; Baek-Yeol Ryoo; Boram Han; Ji Woong Cho; Man Sup Lim; Hyun Lim; Ho Suk Kang; Min-Jeong Kim; Hong Il Ha; Hunho Song; Jung Han Kim; et al. (Gastroenterology Research and Practice)
Background. This retrospective study aimed to assess the efficacy and toxicities of second-line chemotherapy with irinotecan, leucovorin, and 5-fluorouracil (5-FU) in metastatic gastric cancer (MGC) patients previously treated with docetaxel and S-1 with or without oxaliplatin (DS/DOS). Patients and Methods. We reviewed the data of patients who had previously been treated with first-line DS/DOS and received biweekly irinotecan-based chemotherapy (FOLFIRI/IFL) between October 2004 and November 2011. Results. A total of 209 cycles were administered to 35 patients, with a median of 4 (range, 1–22) cycles each. The overall response rate in 29 response-assessable patients was 17.2%, including 2 complete and 3 partial responses. The median progression-free and overall survivals were 3.81 (95% confidence interval [CI], 1.82–5.80) months and 6.24 (95% CI, 1.44–11.04) months, respectively. The major grade 3/4 toxicity was neutropenia (8.6%). Conclusion. FOLFIRI/IFL chemotherapy showed modest antitumour activity and tolerable toxicities in DS/DOS-treated MGC patients.